The Distribution of Advanced Practice Nurses and Population Health in U.S. Frontier Counties - Lynn Jakobs; Jeri Bigbee (Rural Nurse Organization; Binghamton University, 2016)
Residents of frontier counties have disparate access to healthcare due to geographic and economic factors that impact the availability of health care providers and services. The purpose of this study was to evaluate the distribution of Advanced Practice Registered Nurses (APRNS) in U.S. frontier counties and to evaluate the relationship between the presence of APRNs and population health outcomes those counties. The sample included data from 308 frontier counties in 14 states and 858 licensed APRNs residing in those counties. This cross-sectional ecological comparative study utilized the concept of nurse dose to evaluate the relationship between the presence of APRNs and population health outcomes in frontier counties.  Findings include significantly lower premature death and teen birth rates in frontier counties where APRNs or physicians are present.    Keywords:  Frontier, Advanced practice nurses, Rural/Remote